The Gift - Sturgis, Melvin; Fuqua, Robert, 1905-1959 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Gift" by Melvin Sturgis is a science fiction novel written in the early 1950s. The narrative centers on a boy named Carl Sloan, who possesses the miraculous ability to heal others. However, this extraordinary power leads him to face persecution and misunderstanding from society, which views his gifts as a threat rather than a boon. The story unfolds in a courtroom setting, where Carl's past is examined in light of a tragic incident that resulted in several deaths during a chaotic public demonstration of his healing powers. Through various witnesses, including childhood acquaintances and school officials, we learn how Carl's gifts isolated him rather than fostered relationships, leading to his eventual institutionalization. As he matures, he struggles with the repercussions of his abilities and the difficult relationship he has with a society that deems him dangerous. The book explores themes of acceptance, the nature of miracles, and society's fear of those who are different, culminating in a poignant and unsettling conclusion as Carl's fate is sealed by a system unwilling to comprehend his true nature. (This is an automatically generated summary.)
Release date is 2021-05-10
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Healers -- Fiction; Trials -- Fiction; Psychic ability -- Fiction